Género y Generación X. L’identità femminile nella Generazione X spagnola - Matteo Lobina (Confluenze, 2017)
Spanish Generation X writers manipulate the speed of the present and the dialogue between literature and reality. It is a movement filled with violence, brands and hyperreality, and it is often misread as a men’s movement. This paper explores the ironic introduction of the reality show language inside the novel by Gabriela Bustelo and Lucía Etxebarria’s metafictional games, challenge gender roles and the construction of female identity, an identity filtered by technology. This virtual identity reflects a desire to create a literary space where reality is set through fiction.